2009
DOI: 10.4067/s0718-07642009000400010
|View full text |Cite
|
Sign up to set email alerts
|

Tratamiento de Agua para Consumo Humano con Alto Contenido de Arsénico: Estudio de un Caso en Zimapán Hidalgo-México

Abstract: El presente estudio tiene por objeto demostrar que las propiedades fisicoquímicas de la roca Caliza Soyatal, localizada en la región de Zimapán Hidalgo (México), facilitan los niveles de adsorción de arsénico cuando la roca se pone en contacto con el agua contaminada, reduciendo considerablemente las concentraciones de dicho metal. Aunque la roca Soyatal contiene arsénico, las pruebas de desorción efectuadas indican niveles mínimos de dicho fenómeno. Las pruebas se realizaron usando torres empacadas con la roc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…On the other hand, there are also investigations that with other alternatives present lower percentages of removal of this element, for example, Tabaraki & Heidarizadi, (2018) [ 42 ], using a brown alga S. glaucescens presented a bioabsorption efficiency of 62.06% for As (III) and 71.82% for As (V); Verma et al (2019) [ 69 ], produced two citrus limmeta biosorbents, PAC-500 and PPAC-500, with which they eliminated 72.5% As (III), 76.4% As (V) for the first, and the second 61.7% As (III), 76.35% As (V); and Flores, (2009) [ 70 ], removed 89.45% arsenic with 1 g of Soyatal rock.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, there are also investigations that with other alternatives present lower percentages of removal of this element, for example, Tabaraki & Heidarizadi, (2018) [ 42 ], using a brown alga S. glaucescens presented a bioabsorption efficiency of 62.06% for As (III) and 71.82% for As (V); Verma et al (2019) [ 69 ], produced two citrus limmeta biosorbents, PAC-500 and PPAC-500, with which they eliminated 72.5% As (III), 76.4% As (V) for the first, and the second 61.7% As (III), 76.35% As (V); and Flores, (2009) [ 70 ], removed 89.45% arsenic with 1 g of Soyatal rock.…”
Section: Resultsmentioning
confidence: 99%
“…The mean results of water quality before and after biosorption of studied water samples are shown in Table 1 . The water sample studied area is highly contaminated with As (0.6 mg/L) due to a natural contamination of the subterranean water [ 32 – 34 ], which indicated that it was out of the maximum allowable limit for drinking water (0.05 mg/L), according to NOM-127-SSA1-1994. Currently, it is 0.025 mg/L, according to NOM-127-SSA1-1994-2000 (1994) [ 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Garden polyethylene hose (1.27 cm diameter) packed with rocks with diameters ranging 0.84 to 1 mm decreased As content from 200 μg L −1 to 25 μL −1 in the first 2 min. However, the concentration in the outflow increased up to 100 μg L −1 As after one hour (Armienta et al, 2009;Flores et al, 2009).…”
Section: Arsenic Removal By Indigenous Limestone In a Mining Zone Of ...mentioning
confidence: 99%